Juan Crisostomo Lafinur, the First Philosophy Professor Without a Cassock in Buenos Aires. Course Taught in 1819 at the Colegio de la Unión del Sud - Cristina Ambrosini (Perspectivas Metodológicas​)
This article reviews the publication, in 1938 by the Institute of Philosophy of the Faculty of Philosophy and Letters of the University of Buenos Aires, of the Philosophical Course taught by Juan Crisóstomo Lafinur at the recently created Colegio de la Unión del Sud in 1819, Buenos Aires. The editor and prologue of this book, Delfina Varela Dominguez de Ghioldi, consider this course the ideological antecedent of the creation of the University of Buenos Aires. Three years before signing the founding edict of the University of Buenos Aires, together with Bernardino Rivadavia, in 1821, Juan Martín de Pueyrredón appointed the young professor Lafinur to teach philosophy courses at the recently created Colegio de la Unión del Sud, which replaced the old Colegio de San Carlos, founded by Viceroy Vértiz. There, for the first time in Buenos Aires, classes in logic and metaphysics were taught outside of scholastic canons and based on authors identified with modernity, especially citing authors such as Condillac, Locke, Voltaire, and Rousseau in support of their ideas. At the same time, this text highlights Lafinur's tragic fate, marked by exile and premature death in Chile at the age of 27. Finally, we allude to the memory of Jorge Luis Borges, linked to Lafinur by blood ties and intellectual affinity when he considers him a contemporary author, since he highlights the relevance of his ideas and to whom he pays tribute in a poem.